Кодування як засіб захисту інформації у системах контролю доступу з використанням логіко-часових функцій у формі поліномів і біометричних даних суб’єктів - Сачанюк-Кавецька, Н.В. (Реєстрація, зберігання і обробка даних, 2018)
Розглянуто можливість циклічного кодування та правила побудови ключів асиметричного криптоалгоритму на базі ідентифікаційних логіко-часових функцій, що містять усі важливі характеристики переданих повідомлень. Для доступного формального опису такого кодування та правил побудови ключів використано подання логіко-часових функційу формі поліномів. Рассмотрена возможность циклического кодирования и правила построения ключей ассиметричного криптоалгоритма на основе идентификационных логико-временных функций, содержащих все важные характеристики переданных сообщений. Для формального описания такого кодирования и правил построения ключей использовано представление логико-временных функций в форме полиномов. One of the main elements of the integrated information security system is the subsystem of access’s control to information resources. Recently, more attention is attracted by biometrics as one of the newest information technologies that use the unique characteristics of object identification and verification. Therefore, the question of the protection of information resources from unauthorized administrative actions and access by unauthorized persons or programs to computer data is important.Relevant is the preservation of confidentiality of information processed or stored in computer systems. External influences generally oppose using a variety of software and hardware protection methods. The content of the methods of the protective transformations is that the information stored in the system and is transmitted by communication channels, is turns into a cryptogram — a closed (encrypted) text or graphic image documents. The basis for the encryption is based on two elements: a cryptographic algorithm and key. The security of generic algorithms is determined by the key length. In asymmetric algorithms, the encryption and decryption can be performed with different keys. Such algorithms require significantly more computation time, but do not create problems during key distribution. The most promi-sing data protection systems today are considered an asymmetric system with a public key. The last deca-de a great attention of scientists in the field of information security pay biometric. A biometric system can operate in modes of verification and identification. All of these approaches protect the information easy enough to implement in the time-logic environment, making all the settings required for message transform on the time-logic functions.The possibility of cyclic encoding and the rules for constructing key asymmetric crypto algorithm on the basis of the identification time-logic functions, which contain all the important characteristics of transmitted messages, is analyzed. Available for the formal description of this encoding and the rules of construction keys used in the representation of time-logic functions in the form of polynomials.